Requirements for activation of the herpes simplex virus glycoprotein C promoter in vitro by the viral regulatory protein ICP4. - Gu, B (1994)
During infection with herpes simplex virus, infected-cell polypeptide 4 (ICP4) activates transcription of most herpes simplex virus genes. In the present study, the mechanism of activation of transcription by ICP4 was investigated by using a reconstituted in vitro system with fractionated and purified general transcription factors, coupled with DNA-binding assays. The templates used in the reactions included regions of the gC and thymidine kinase (tk) promoters in plasmids, and on isolated fragments, allowing for the evaluation of the potential function of naturally occurring and inserted ICP4-binding sites and elements of the core promoter. ICP4 efficiently activated transcription of the gC promoter by facilitating the formation of transcription initiation complexes. ICP4 could not substitute for any of the basal transcription factors. Moreover, TATA-binding protein (TBP) could not substitute for TFIID in activation, suggesting a requirement for TBP-associated factors. Interactions between ICP4 and DNA 3' to the start site was necessary for activation of the gC promoter. The requirement for DNA-protein contacts could be met either by the presence of an ICP4-binding site in the gC leader, by the presence of a site more than 150 nucleotides further downstream, by an inserted site that normally acts to repress transcription, or by the addition of sufficient non-site-containing DNA. The gC TATA box and start site, or initiator element (inr), were individually sufficient for activation by ICP4 and together contributed to optimal activation. In contrast to gC, the tk promoter was poorly activated in the reconstituted system. However, the tk TATA box was efficiently activated when the tk start site region was replaced with the gC inr, suggesting that activation was mediated through the inr and inr-binding proteins. In addition, mutation of the inr core resulted in a gC promoter that was very poorly activated by ICP4. The results of this and previous studies demonstrate that ICP4 activates transcription in a complex manner involving contacts with DNA 3' to the start site, TBP, TFIIB, TBP-associated factors, and possibly proteins functioning at the start site of transcription.